Development of an algorithm for correlation of aircraft positioning data from radar and ADS-B sensors / Koh Che Hun - Koh , Che Hun (2019)
The Multi-radar Tracking System (MRTS) is implemented in aircraft surveillance with high confidence in terms of reliability and safety in Air Traffic Control (ATC) centers worldwide. The MRTS integrates two types of radar: Primary Surveillance Radar (PSR) and Secondary Surveillance Radar (SSR) to produce a Single Integrated Air Picture (SIAP). Its main function is to track aircraft in an airspace by using data from tracks collected from several radars. Advancement in aircraft surveillance sensor technology saw the emergence of new sensors, such as the Automatic Dependent Surveillance Broadcast (ADS-B) and Multilateration systems. Therefore, the radar is no longer the sole technology for air traffic surveillance. The ADS-B enables aircraft, ground vehicles and controllers to exchange positioning information via a dedicated communication link. This realizes unprecedented air-to-air and air-to-ground surveillance capabilities. It also provides surveillance coverage in remote and low altitude areas that are not covered by the radar. A Multi-sensor Tracking System (MSTS) makes use of different type of sensors to produce a SIAP rather than only radar. Hence, the integration of ADS-B into MSTS is gaining interest among researchers in its necessity to enhance the performance of ATC in terms of continuity, integrity, accuracy, and at the same time serves as a backup surveillance sensor. To fuse data from different sensors, the correlation algorithm is vital. Correlation is a process that associates the positioning data from different sensors to keep the SIAP up-to-date. The process needs to take account the differences in performance and characteristic of different sensors. Correlation algorithm aims to resolve ambiguities and conflicting information to provide an operationally useful synthesis of the surveillance data. However, at certain circumstances, ambiguities such as missed tracks, extra tracks or position and velocity errors may occur. Nonetheless, research on the use of MSTS for ATC is still in infancy. Several studies were carried out to apply and improve on existing correlation algorithms involving radars and the new surveillance sensors. Most of these studies are conducted by the Original Equipment Manufacturers (OEM) and hence the findings are not widely available in the public domain. However, findings indicate that there are still lack of effective correlation algorithms to resolve the ambiguities and differences in the multi-sensor data correlation environment. This research aims to develop an effective and high-performance multi-sensor correlation algorithm. To achieve the aim, the work reviews multi-sensor tracker architectures to identify the problems that arise when performing data correlation for multi-sensors; conducts study on existing correlation algorithms available in the public domain for MRTS and MSTS; analyzes the advantages and drawbacks of each algorithms; and derives the vital characteristics of a high-performance correlation algorithm. Based on the findings, a multi-sensor data correlation algorithm is developed. The algorithm is validated using real time radar and ADS-B data from Department of Civil Aviation Malaysia (CAAM).